Katechumenat przedmałżeński narzeczonych - Kulbacki, Piotr (Studia Pastoralne, 2009)
After the restoration of catechumenate in the Church its ideas are still more often applied in a post-baptism formation according indications presented in the 4th chapter of the Rite of Christian Initiation for Adults. New suggestions appeared for marriage preparation since it should be similar to catechumenate. The main rules of catechumenate are considered in this text concerning Christian formation and applied to an initiation to the „Church of the home”. The last should be analogous to Christian initiation, being the pre-marriage catechumenate, as is shown in Familiaris consortio. It is possible to fulfill all the required periods, degrees and celebrations during one year, as it is in formal catechumenate. The article presents pastoral and liturgical foundations for such a formation.